Streamlining data management & process analytics for the manufacturing of cell & gene therapies. Issue 7 (2018) - Bournonville, Sébastien de; Lambrechts, Toon; Pinna, Thomas, Ioannis Papantoniou; Aerts, Jean-Marie
No abstract available